Technology and the good society: A polemical essay on social ontology, political principles, and responsibility for technology. (February 2018) - Coeckelbergh, Mark
Abstract: How can we best theorize technology and the good society? This essay responds to this issue by showing how our assumptions about the meaning of the social and the political influence our evaluations of the impact of new technologies on society, and how, conversely, new technologies also shape the concepts we use to evaluate them. In the course of the analysis, the essay offers a polemic that questions individualist approaches to the good society and individualist assumptions about the social, especially in the analytic-individualist traditions and in postphenomenology, and recommends that more philosophers of technology use the resources of political philosophy to tackle the challenge of understanding and evaluating technology and society.